Syntaxin binding protein 1 is not required for allergic inflammation via IgE-mediated mast cell activation. - Zhengli Wu; Adam J MacNeil; Jason N Berman; Tong-Jun Lin (PLoS ONE, 2013)
Mast cells play a central role in both innate and acquired immunity. When activated by IgE-dependent FcεRI cross-linking, mast cells rapidly initiate a signaling cascade and undergo an extensive release of their granule contents, including inflammatory mediators. Some SNARE (soluble N-ethylmaleimide-sensitive fusion factor attachment protein receptor) proteins and SM (Sec1/Munc18) family proteins are involved in mast cell degranulation. However, the function of syntaxin binding protein 1 (STXBP1), a member of SM family, in mast cell degranulation is currently unknown. In this study, we examined the role of STXBP1 in IgE-dependent mast cell activation. Liver-derived mast cells (LMCs) from wild-type and STXBP1-deficient mice were cultured in vitro for the study of mast cell maturation, degranulation, cytokine and chemokine production, as well as MAPK, IκB-NFκB, and NFAT signaling pathways. In addition, in vivo models of passive cutaneous anaphylaxis and late-phase IgE-dependent inflammation were conducted in mast cell deficient W(sh) mice that had been reconstituted with wild-type or STXBP1-deficient mast cells. Our findings indicate that STXBP1 is not required for any of these important functional mechanisms in mast cells both in vitro and in vivo. Our results demonstrate that STXBP1 is dispensable during IgE-mediated mast cell activation and in IgE-dependent allergic inflammatory reactions.